Spatiotemporal regulation of polar flagellar assembly, chemotaxis and c-di-GMP-dependent signaling in γ-proteobacteria - Schmidt, Lisa Marie; Justus Liebig University Giessen (My University, 2026)
Bacterial motility is a fundamental trait that enables cells to explore their environment and respond to, as well as relocate to, more favorable growth conditions. In many species, motility is achieved by rotating flagellar filaments whose activity is controlled by the chemotaxis system, allowing bacteria to navigate along chemical gradients. In addition to this planktonic lifestyle, bacteria can transition to a sessile state, characterized by surface attachment and biofilm formation. This transition is generally regulated by intracellular second messenger molecules, such as c-di-GMP, with elevated levels promoting a sessile lifestyle by stimulating biofilm formation while simultaneously repressing motility. Consequently, coordination between chemotaxis and second messenger signaling is crucial for balancing motility and surface-associated growth in these bacteria. In this work, the spatiotemporal regulation of polar flagellar assembly, chemotaxis, and c-di-GMP- dependent signaling was investigated in species of the genera Shewanella and Pseudomonas. In S. putrefaciens, polar flagellar assembly was shown to depend on an interaction between the polar landmark protein FlhF and the flagellar C-ring component FliG, mediated by the N-terminal domain of FlhF, termed FID. Furthermore, FlhF was demonstrated to restrict FliG recruitment to the cell pole, through its simultaneous interaction with FliG and HubP. In addition, the function of the HubP homolog FimV was investigated in P. putida. FimV was shown to localize to the cell pole, depending on the presence of both a LysM-like domain and an immunoglobulin-like domain. While deletion of fimV did not affect flagellation, chromosome segregation, or pilus-mediated motility, FimV was required for correct positioning of the chemotaxis system and efficient swimming motility in P. putida. Domain exchange experiments between HubP and FimV from S. putrefaciens and P. putida revealed species-specific functions, indicating distinct adaptations to their respective environments. Moreover, the interaction between the histidine kinase CheA and the phosphodiesterase Pch was investigated in P. putida. Both proteins exhibited polar localization, and their interaction was shown to be mediated by the EAL domain of Pch and a specific region within the unstructured linker region of CheA. While the polar localization of Pch strongly depended on CheA, CheA localization depended on FlhF, PocB, and ParP, and, to a lesser extent, on FimV. Sequence conservation analysis revealed a specialized amino acid sequence of the Pch EAL domain compared to canonical EAL domains, as well as five highly conserved regions within the CheA linker region. This suggests an evolutionarily conserved interaction interface between CheA and Pch, linking chemotaxis and c-di-GMP signaling. Collectively, these results provide new insights into the spatiotemporal organization of flagellar assembly and chemotaxis signaling, highlighting the role of polar organizer proteins and signaling components in coordinating bacterial motility and transitions between motile and sessile states.
Keywords: ddc:570